Las víctimas del conflicto en Colombia.: Apuntes para una ética anamnética (Theological Kronos, 2019)
In an armed conflict, such as the Colombian one, the victimization of civil society is increasing as well as the casualties of the groups directly involved as combatants, and this situation is justified from the different edges of the conflict as an inevitable part of the conflict, “Collateral damage”, a victimization necessary to advance the confrontation and the achievement of the objectives of each actor. Victims who suffer such victimization emerge in confrontation with this logic of conflict and propose, from the construction of memory, a critical ethical stance. It is a question of showing, in this situation, the emergence of this ethic from the collective memory of the victims, whose proposal is presented as an anamnestic ethic. This ethic challenges and is proposed in confrontation with the official memory, with pretensions of being hegemonic, and as an alternative in the journey towards a horizon of national reconciliation.
Keywords: Armed conflict; Victims in Colombia; Anamnestic Ethics; Collective memory